Collaborative destination marketing and PWYW. (May 2018) - Stangl, Brigitte; Prayag, Girish
Highlights: Results show potential of innovative pricing for collaborative marketing efforts. Minimum, maximum and PWYW prices for self-selected tourist packages assessed. PWYW resulted in higher prices paid by tourists than traditional list prices. Limited differences revealed between satisfied and dissatisfied tourists on prices. Collaboration between providers at destination can increase profitability using PWYW.